Assessment of clinical metabolic risk score and its correlation with anthropometric and biochemical parameters in adults aged over 30 years: a cross-sectional study in a rural setting - Verma, Monesh; Patidar, Gourav (International Journal Of Community Medicine And Public Health, 2025)
Background: Metabolic syndrome and related non-communicable diseases are emerging as significant health concerns, particularly among adults aged over 30 years. The Clinical Metabolic Risk Score (CMRS) is a useful composite tool to quantify cardiometabolic risk in populations. This study aims to assess CMRS and determine its correlation with anthropometric and biochemical parameters among adults aged over 30 years in a rural setting. Methods: A community-based cross-sectional study was conducted among 300 adults aged above 30 years attending the outpatient department (OPD) in a rural community health centre. Anthropometric parameters such as Body Mass Index (BMI), waist circumference, and waist-hip ratio were measured. Biochemical assessments included fasting blood glucose, serum triglycerides, high-density lipoprotein (HDL) cholesterol, and blood pressure. The CMRS was calculated based on standard risk thresholds. Results: A significant positive correlation was observed between CMRS and BMI (r=0.62, p<0.001), waist circumference (r=0.57, p<0.001), fasting glucose (r=0.49, p<0.001), and serum triglycerides (r=0.44, p<0.001). An inverse correlation was noted with HDL cholesterol (r= -0.39, p<0.01). Participants with higher CMRS values demonstrated increased prevalence of central obesity and impaired fasting glucose (p<0.01). Conclusions: The CMRS is a reliable tool for assessing metabolic risk in adult populations. It depicts strong associations with standard anthropometric and biochemical risk indicators, supporting its use in early identification and intervention planning.